2018
DOI: 10.1002/cne.24593
|View full text |Cite|
|
Sign up to set email alerts
|

Mediolateral and dorsoventral projection patterns of cutaneous afferents within transverse planes of the mouse spinal dorsal horn

Abstract: The central projection patterns of cutaneous afferents from the forelimb and shoulder of mice were studied in the spinal dorsal horn after intracutaneous injection of AlexaFluor 488-conjugated and/or 594-conjugated cholera toxin subunit B (CTB). Based on their dermatomes, the following eight skin regions are thought to be innervated by spinal nerves from the sixth to eighth cervical spinal nerve roots: the dorsal surface of the shoulder, brachium, proximal forearm, distal forearm, hand, palmar surface of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…The transganglionic axon terminals associated with LR3 locate more medially in the spinal dorsal horn than that of LR8, and the motor neurons associated with LR3 are situated more laterally on the spinal ventral horn than that of LR8. These segmental and regional distribution is accorded with the “somatotopic arrangement” in the CNS of rats, which has been well defined in the previous studies ( Swett and Woolf, 1985 ; Maslany et al, 1991 , 1992 ; Takahashi et al, 2010 ; Odagaki et al, 2019 ). Increasing pieces of evidence from the human have proved that “somatotopic arrangement” does not only exist on the cerebral cortices but is also present in the spinal cord ( Standring, 2008 ; Stroman et al, 2012 ; Willoughby et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…The transganglionic axon terminals associated with LR3 locate more medially in the spinal dorsal horn than that of LR8, and the motor neurons associated with LR3 are situated more laterally on the spinal ventral horn than that of LR8. These segmental and regional distribution is accorded with the “somatotopic arrangement” in the CNS of rats, which has been well defined in the previous studies ( Swett and Woolf, 1985 ; Maslany et al, 1991 , 1992 ; Takahashi et al, 2010 ; Odagaki et al, 2019 ). Increasing pieces of evidence from the human have proved that “somatotopic arrangement” does not only exist on the cerebral cortices but is also present in the spinal cord ( Standring, 2008 ; Stroman et al, 2012 ; Willoughby et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…A similar relationship was observed between axon terminals from S1c and cutaneous afferents from the trunk (Figures d and ). We also observed the somatotopic organization of the cutaneous afferents in the spinal dorsal horn: afferents from the digits and palm projected more medially than those from the rest of the forepaw, and those from the forearm and brachium terminated between the “forepaw” and “trunk” areas in the dorsal horn (Odagaki, Kameda, Hayashi, & Sakurai, in press). Together with those observations, our results in this study suggest that the projection areas of S1r axons overlap those of afferents from the digits, palm, and dorsal surface of hand, while the projection areas of S1c axons overlap those of afferents from the brachium and trunk region.…”
Section: Discussionmentioning
confidence: 80%
“…to the CNS. [17][18][19][20][21] Their successive neural connections with the corresponding targets in the spinal cord, thalamus, and cerebral cortex was not determined in the current study. In 2016 and 2018, results from functional magnetic resonance imaging (fMRI) studies indicated that acupuncture stimulation at LR 3 can specifically activate or deactivate the visual, motor, and sensory cortices, etc., while stimulating both LI 4 and LR 3 can modulate activities of cognition-related brain regions in patients with Alzheimer's disease.…”
mentioning
confidence: 76%
“…to the spinal dorsal horn and brainstem, as well as motor efferents from the spinal ventral horn. [17][18][19][20][21] As a comparison, innervation on acupuncture points located on the head and face is more complicated. 6,11 For example, GB 14, ST 2, and ST 6 establish their sensory connections with the trigeminal ganglion, cervical DRG, spinal trigeminal nucleus, and cervical spinal dorsal horn via trigeminal and spinal sensory pathways, as well as making motor connections with the facial nucleus, motor trigeminal nucleus, and cervical spinal ventral horn via trigeminal, facial and spinal motor pathways.…”
mentioning
confidence: 99%